Milan Kundera & feminism dangerous intersections - O'Brien, John (St. Martin's Press, 1995)
Initially, O'Brien takes Kundera to task for representing women from a perspective dominated by either/or, opposition-based frameworks. Instead of dismissing Kundera as sexist, however, O'Brien takes these concerns further, arguing that a feminist-postmodernist approach shows Kundera exposing, not reinforcing, the misrepresentation of women. Using an eclectic perspective that draws on the insights of feminist criticism and deconstruction, the author looks to strong women, such as The Unbearable Lightness of Being's Sabina in order to develop a method of simultaneously appreciating the complicated surfaces and the paradoxical depths of Kundera's work. Considering O'Brien's own cross-purpose and Kundera's famous penchant for ambiguity, the duality of O'Brien's conclusions are appropriate. Milan Kundera & Feminism considers Kundera's contributions to the feminist critique of representation without ignoring the serious difficulties for the feminist reader